(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2025)
The region between the Tagus and the Guadiana is notable for the Southwestern stelae, one of the earliest written cultures of the Iberian Peninsula, active between the 6th and 4th centuries BC. The subsequent record, prior to the introduction of Latin, has scarcely been studied and reveals a marked heterogeneity of media, languages and scripts. Epigraphic, archaeological and literary evidence from the two centuries before the turn of the Era reflect a complex social and cultural landscape upon which Romanisation took root. This paper addresses the methodological challenges of reconstructing the pre-Roman linguistic and cultural history of the southwest, with particular emphasis on the process of Latinisation.